2007
DOI: 10.1158/0008-5472.can-06-3813
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Is Central to the Expression of Truncated Neurokinin-1 Receptor in Breast Cancer: Implication for Breast Cancer Cell Quiescence within Bone Marrow Stroma

Abstract: Breast cancer is a leading cause of mortality among women in the United States. Tac1 and neurokinin-1 (NK1) are involved in autocrine stimulation of breast cancer cells (BCCs). The single NK1 gene produces full-length (NK1-FL) and truncated (NK1-Tr) forms. NK1-Tr mediates malignancy in breast cells. We now report a critical role for nuclear factor-KB (NF-KB) in the expression of NK1-Tr, but not NK1-FL, in human BCCs. By Western and Northern blot analyses, NK1-FL and NK1-Tr were coexpressed in BCCs but were und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…A study by Ramkissoon et al (24) showed that the expression of tr-NK-1R is dependent upon the activation of the proinflammatory transcription factor NF-κB in breast cancer cell lines in vitro. NF-κB is activated by a number of inflammatory signals present in UC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Ramkissoon et al (24) showed that the expression of tr-NK-1R is dependent upon the activation of the proinflammatory transcription factor NF-κB in breast cancer cell lines in vitro. NF-κB is activated by a number of inflammatory signals present in UC.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the hypoxia, inflamed mucosa have increased vascularity compared with normal tissue, potentially due to increased vascular endothelial growth factor, an HIF-1α downstream target (40). The mucosal hypoxia characteristic of UC is interesting in light of research showing hypoxia can activate NF-κB (42,43), which is capable of specifically increasing expression of tr-NK-1R (24). In addition, hypoxia has been shown to induce alternative splicing events in other genes in vitro, and these splice variants are also associated with mutations to the tumor suppressor p53, a common finding in CAC (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, until recently, little attention has been given to the different splice variants of NK1R. Previous studies pointed out the central role of NK1R-tr in breast cancer (104,105). Likewise, Gillespie et al analyzed NK1R-tr and NK1R-fl in colitis-associated cancer and found that it was the expression of NK1R-tr alone that predicted the progression from quiescent colitis to highgrade dysplasia and cancer (106).…”
Section: Therapeutic Innovations In Hepatoblastoma the Nk1r As A Tumomentioning
confidence: 99%
“…Compared with full-length (fl-TACR1), tr-NK1R lacks 96 amino acids at the cytoplasmic C-terminus of the receptor that are responsible for intracellular signal transduction. Although this splice variant is considered to be able to couple G proteins, it exhibits decreased efficiency with respect to internalization and desensitization (8,(13)(14)(15). The net result of this is a decreased ability for negative feedback inhibition, allowing constant activation despite saturation of the receptor complex (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%